2014
DOI: 10.1051/0004-6361/201322362
|View full text |Cite
|
Sign up to set email alerts
|

Search for a habitable terrestrial planet transiting the nearby red dwarf GJ 1214

Abstract: High-precision eclipse spectrophotometry of transiting terrestrial exoplanets represents a promising path for the first atmospheric characterizations of habitable worlds and the search for life outside our solar system. The detection of terrestrial planets transiting nearby late-type M-dwarfs could make this approach applicable within the next decade, with soon-to-come general facilities. In this context, we previously identified GJ 1214 as a high-priority target for a transit search, as the transit probabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 57 publications
(102 reference statements)
2
83
0
Order By: Relevance
“…Finally, Murgas et al (2012) found a radius of GJ 1214 b at the Hα line higher than the radii measured at nearby continua, but the difference is not statistically significant. The latest observations reported by Teske et al (2013), Colón & Gaidos (2013), Wilson et al (2014), Gillon et al (2014), de Mooij et al (2013, and Kreidberg et al (2014) have agreed in showing a featureless spectrum, favoring high mean molecular mass compositions. In that context, recently Kreidberg et al (2014) ruled out the cloud-free high molecular weight atmosphere scenario for GJ 1214b with a high statistical significance.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Finally, Murgas et al (2012) found a radius of GJ 1214 b at the Hα line higher than the radii measured at nearby continua, but the difference is not statistically significant. The latest observations reported by Teske et al (2013), Colón & Gaidos (2013), Wilson et al (2014), Gillon et al (2014), de Mooij et al (2013, and Kreidberg et al (2014) have agreed in showing a featureless spectrum, favoring high mean molecular mass compositions. In that context, recently Kreidberg et al (2014) ruled out the cloud-free high molecular weight atmosphere scenario for GJ 1214b with a high statistical significance.…”
Section: Introductionmentioning
confidence: 61%
“…Bottom: same data set after removing the new ephemeris, including its 1-σ errors (dashed lines). Teske et al (2013), Gillon et al (2014), Colón & Gaidos (2013), Fraine et al (2013), and our measurements are shown in Fig. 12.…”
Section: Transit-timing Observationsmentioning
confidence: 71%
See 1 more Smart Citation
“…Following Gillon et al (2014), the instrumental models included three types of low-order polynomials. The first had as variables the x-and y-positions of the centre of the PSF to represent the pixel phase effect of the IRAC InSb arrays (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Since its discovery, many groups have published measurements of GJ1214bʼs transmission spectrum in the optical and nearinfrared (Bean et al 2010Croll et al 2011;Crossfield et al 2011;Désert et al 2011;Berta et al 2012;de Mooij et al 2012de Mooij et al , 2013Murgas et al 2012;Colón & Gaidos 2013;Fraine et al 2013;Narita et al 2013;Teske et al 2013;Cáceres et al 2014;Gillon et al 2014;Kreidberg et al 2014;Wilson et al 2014;Nascimbeni et al 2015). A total of 58 measurements have been published for bandpasses with central wavelengths shorter than 9260Å, the longest wavelength in our Magellan/ IMACS spectrum.…”
Section: Previous Measurementsmentioning
confidence: 99%